Le cancer de la thyroïde métastatique: développement d’une crise thyréotoxique et comportement des composés iodés dans le sérum après le traitement de métastases fonctionellement actives dans les poumons avec d’iode radioactif - Němec, J.; Bednář, J.; Váňa, S.; Soumar, J.; Soutorová, M. (Nuklearmedizin - NuclearMedicine, 1969)
The authors describe a case of thyrotoxic crisis caused by the destruction with radioiodine of functionally active pulmonary metastases of a thyroid tumour. The toxic symptoms receded spontaneously after mere supporting treatment.